2008
DOI: 10.1017/s0007114507853414
|View full text |Cite
|
Sign up to set email alerts
|

Inulin results in increased levels of β-catenin and cyclin D1 as the adenomas increase in size from small to large in the Min/+ mouse

Abstract: The mechanism that drives the growth of some colonic adenomas towards malignancy, while permitting others to remain for decades in quiescence, remains unknown. Diets can alter the growth rate of intestinal tumours but it is still unknown whether diets are able to alter the molecular biology of these adenomas in a way that predicts further outcome. To address this issue we fed Min/þ mice with two diets known to lead to different adenoma outcomes: a high-fat control diet (n 15) or a high-fat inulin-enriched (10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…This consideration is in accord with the “butyrate paradox,” which argues that the ability of this SCFA to promote or impede cell proliferation is contextually dependent on the cell-type, time, and the amount of exposure (Donohoe et al, 2012). The doses of SCFA exceeding the threshold tolerable by the host have been shown to aggravate colonic inflammation (Kaiko et al, 2016; Kim et al, 2013) and tumorigenesis (Belcheva et al, 2014; Misikangas et al, 2008; Pajari et al, 2003), induce urethritis and hydronephrosis (Park et al, 2016), and promote obesity by aggravating hepatic lipogenesis (Singh et al, 2015) and hyperphagia (Perry et al, 2016). Janssen et al (2017) reported that feeding of guar gum (a soluble fiber comprised of mannose [β 1,4-linked] and galactose [1,6-linked]) for 18 weeks protected mice from diet-induced obesity but eventuated hepatic inflammation and fibrosis associated with increased plasma TBA and disrupted enterohepatic circulation).…”
Section: Discussionmentioning
confidence: 99%
“…This consideration is in accord with the “butyrate paradox,” which argues that the ability of this SCFA to promote or impede cell proliferation is contextually dependent on the cell-type, time, and the amount of exposure (Donohoe et al, 2012). The doses of SCFA exceeding the threshold tolerable by the host have been shown to aggravate colonic inflammation (Kaiko et al, 2016; Kim et al, 2013) and tumorigenesis (Belcheva et al, 2014; Misikangas et al, 2008; Pajari et al, 2003), induce urethritis and hydronephrosis (Park et al, 2016), and promote obesity by aggravating hepatic lipogenesis (Singh et al, 2015) and hyperphagia (Perry et al, 2016). Janssen et al (2017) reported that feeding of guar gum (a soluble fiber comprised of mannose [β 1,4-linked] and galactose [1,6-linked]) for 18 weeks protected mice from diet-induced obesity but eventuated hepatic inflammation and fibrosis associated with increased plasma TBA and disrupted enterohepatic circulation).…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, in models applying AOM, the AOM precursor dimethyl hydrazine (DMH) or AOM/dextran sodium sulfate (DSS) to induce carcinogenesis, anti-tumorigenic effects of inulin have been found in mice [ 21 , 50 ] and rats when administered prior and subsequent to the carcinogen [ 51 55 ]. In conventional C57BL/6J Min/+ mice, inulin has been reported to increase the genetically driven small intestinal tumor burden [ 56 58 ] except for one study reporting short chain FOS (which can be produced by degradation of inulin) to attenuate tumorigenesis [ 59 ]. These data may suggest a different role of fructose based fiber (inulin and FOS) in the genetically driven small intestinal tumorigenesis in C57BL/6J Min mice compared with carcinogen induced colon tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Mice that developed hyperbilirubinemia upon ICD diet displayed loss in gut bacteria richness and diversity, reduced Tenericutes, and increased abundance of Proteobacteria and Clostridia, which are capable of producing butyrate and secondary bile acids. Notably, butyrate is involved in the promotion or inhibition of cell proliferation based on the amount and duration of exposure and the type of target cell 107 and excessive doses may exert oncogenic effects, promote liver steatosis and intestinal inflammation, 108112 whereas secondary bile acids have known hepatotoxic activity. 113 The metabolomic analysis showed that an increase in butyrate cecal content characterized mice with hyperbilirubinemia and HCC.…”
Section: The Gut Microbiota and Hccmentioning
confidence: 99%